UNDERSTANDING ZINA LAW IN INDONESIA (After the Ratification of the Criminal Code Bill Becomes Law Number 1 of 2023 About the Criminal Code) - Suprayogi, Rizqi (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to find weaknesses in law enforcement related to the problem of adultery in Indonesian laws as well as to provide solutions so that the law can be upheld. This research was made using library research research which in its implementation collected sources of books, laws and the internet. The results of this study indicate that adultery is a public crime that has an impact on the perpetrators, family and society. The act of adultery is contrary to socio-cultural customs and religion. The perpetrators of adultery must be punished according to statutory regulations according to Law Number 1 of 2023 concerning the Criminal Code. Even though there are still weaknesses in the law, customary law can play a role in encouraging the perpetrators of adultery to be entangled in the law. Through the customary wisdom of the community.